Mortality among amphetamine users with hepatitis C virus infection: A nationwide study. - Caroline Gahrton (Public Library of Science (PLoS), 2021)
Aims To investigate liver-related and all-cause mortality among amphetamine users with hepatitis C virus (HCV) infection and compare this with opioid users with HCV infection and the uninfected general population. Methods In this national register study of mortality in persons notified with HCV infection 1990-2015 and a substance-related diagnosis in Sweden, amphetamine users (n = 6,509) were compared with opioid users (n = 5,739) and a matched comparison group without HCV infection/substance use (n = 152,086). Results Amphetamine users were observed for 91,000 years and 30.1% deceased. Crude liver-related mortality was 1.8 times higher in amphetamine users than opioid users (crude mortality rate ratio 1.78, 95% CI 1.45-2.19), but there was no significant difference when adjusting for age and other defined risk factors. An alcohol-related diagnosis was associated with liver-related death and was more common among amphetamine users. Crude and adjusted liver-related mortality was 39.4 and 5.8 times higher, respectively, compared with the uninfected group. All-cause mortality was lower than in opioid users (adjusted mortality rate ratio 0.78, 95% CI 0.73-0.84), but high compared with the uninfected group. External causes of death dominated in younger ages whereas liver-related death was more common among older individuals. Conclusions This national register study presents a higher crude risk of liver-related death among HCV-infected amphetamine users compared with opioid users or the uninfected general population. The higher risk of liver-related death compared with opioid users may be explained by lower competing death risk and higher alcohol consumption. Treatment of HCV infection and alcohol use disorders are needed to reduce the high liver-related mortality.